PENGEMBANGAN DAN MANAJEMEN BADAN USAHA MILIK DESA (BUMDES) DI DESA NEPA MEKAR KABUPATEN BUTON TENGAH - Rais. R, Muhammad; Adan, L.M. Hasrul; Hasni, Hasni (INCIDENTAL : Journal Of Community Service and Empowerment, 2024)
Community Service in Nepa Mekar Village aims to; (1) Equip BUMDes managers in Nepa Mekar village with the practical skills needed to run the business in a professional and transparent manner; (2) Increase transparency and accountability in the financial management of BUMDes Nepa Mekar through a simple and easily accessible bookkeeping system (3) Improve the quality of human resources of BUMDes managers in Nepa Mekar village. This service will be implemented in Nepa Mekar Village, Lakudo District, Central Buton Regency, and will involve training, lectures, and a Focus Group Discussion (FGD) approach. The findings basically show that each initiative implemented is closely related to the needs of Nepa Mekar Village, Lakudo Sub-district, Central Buton District. This became the background for the implementation of a number of excellent procurement programs for both parties. Thus, various PKM programs can be implemented and run in accordance with the expected goals.